Artificial experts : social knowledge and intelligent machines - Collins, H. M. (Harry M.), 1943-; IEEE Xplore (Online Service); MIT Press (Cambridge, Massachusetts : MIT Press, 1990)
In Artificial Experts, Collins explains what computers can't do, but he also studies the ordinary and extraordinary things that they can do. He argues that the machines we create are limited because we cannot reproduce in symbols what every community knows, yet we give our machines abilities by the way we embed them in our society. He unfolds a compelling account of the difference between human action and machine intelligence, the core of which is a witty and learned explanation of knowledge itself, of what communities know and the ways in which they know it. H. M. Collins is Professor of Sociology, Head of the School of Social Sciences, and Director of the Science Studies Centre at the University of Bath.
Includes bibliographical references (p. [251]-258) and index.
Also available in print.
Mode of access: World Wide Web
Description based on PDF viewed 12/29/2015.
Keywords: Artificial intelligence -- Social aspects; Knowledge, Sociology of; Expert systems (Computer science); Electronic books